Skötselns och ståndortens betydelse för kärnvedsbildningen i tall - Fahlgren, Steve; Jansson, Tomas (2010)
Heartwood has always been a desirable part of the tree, due to it’s superior decay qualities com-pared to the sapwood. How the formation of heartwood works has been known for a long time, but which factors that initiates and stimulates the production are poorly understood. This case study presents the results of a study in which silvicultural treatments and site properties had a key position as factors to the formation of heartwood. According to the hypothesis the amount of sapwood is directly controlled by the size of the crown. The amounts of heartwood in four Scots pine stands, including a dense low quality site, a low density high quality site, and two in be-tween, was examined by extraction of core samples. According to the hypothesis dense stands at low quality sites would develop small crowns with a little need of sapwood, and therefore a larger need of heartwood. The results basically showed that dense stands on poor sites had a bigger proportion of heartwood than low density stands on high quality sites, but the widths of the growth rings seems to be an important factor as well. However, the variation in, and especially between, the stands are large, and therefore it is difficult to draw any conclusion. The results are, nevertheless, discussed against existing theories and other field trials that had similar results.